The Role of Interactive Multimedia in Islamic Religious Education Learning at SDN 018 West Balikpapan - Yuningsih, Hesti; Haeruddin , Hendra (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
Education is a conscious and planned effort to develop students' personalities through a learning environment and the process of learning. In the digital era, the use of interactive multimedia in education is relevant and important. This research aims to develop and evaluate the validity of interactive multimedia in enhancing interest and learning outcomes in Islamic Religious Education (PAI) at SDN 018 Balikpapan Barat. The research methods used are observation, interviews, and documentation. The results of the research show that the use of interactive multimedia in education has significant benefits, such as increasing students' interest and learning outcomes, enriching the learning experience, saving time and space, improving the quality of student learning, and encouraging active student engagement in the learning process. Although there are still challenges in the use of interactive multimedia at SD 018 Balikpapan Barat, with proper development and implementation, interactive multimedia has great potential to enhance learning in the school.